BSCI-27. MELATONIN REDUCES MALIGNANCY OF BREAST CANCER BRAIN METASTATIC CELLS. (12th August 2019) - Gil, Beatriz Fernandez; Rodriguez, Katherine; Schiapparelli, Paula; Ramos, Carla Vazquez; Escames, Germaine; Quinones-Hinojosa, Alfredo; Sarabia-Estrada, Rachel
Abstract: Around fifteen to thirty percent of stage IV breast cancer metastasizes to the brain, severely decreasing the quality of life of these patients by causing neurological decline and eventually death. In metastatic cancers there is a small subset of cells in the primary tumor bulk called Metastatic Tumor Initiating Cells (MTICs) which are able to escape and produce a niche establishment at distal sites where they can quickly become resistant to surgery and radiation. Melatonin has shown an inhibitory role in the viability and invasiveness of breast cancer and in modulating the expression of proteins related to Breast Cancer Stem Cells (BCSCs). These findings suggest its potential anti-metastatic role in different breast cancer cell lines. In this study we aimed to evaluate the effects of melatonin treatment in vitro for breast cancer brain metastasis. The cell line MDA-BT was originally obtained from MDA-MB-231, passed through the rat's heart and then isolated once engrafted as a tumor in the brain. After a dose response assay, cells were treated with melatonin at doses of 1500 and 3000 µM for 48hrs. Clonogenic assay, MTT, as well as a stem cell signature through RT-qPCR, including CD44, CD24 and ALDH1 markers, were performed to evaluate the malignancy of the MTICs. The results showed that melatonin at high doses impacts morphology, declines viability, reduces colony formation ability, and decreases stemness in MDA-BT cells. Therefore, our findings highlight melatonin as a relevant therapeutic candidate to target breast cancer brain metastases.